2012
DOI: 10.7314/apjcp.2012.13.11.5557
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Auto-antibodies to Survivin and MUC1 Variable Number Tandem Repeats in Colorectal Cancer

Abstract: Aim: The aim of this study was to investigate the frequency and correlation between auto-antibodies to survivin and MUC1 variable number tandem repeats (VNTR) in colorectal cancer (CRC), which can provide valuable information for the design of immunotherapeutic vaccines for this disease. Methods: Enzyme-linked immunosorbent assays (ELISA) were used to examine the level of auto-antibodies against survivin and MUC1 VNTR in the serum of 135 CRC patients and 95 healthy volunteers. Results: Using mean absorbance + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Survivin antibodies were noted in 39.7% of all cancers studied, including 33% cases of CRC, hepatoma and esophageal cancer, 40% of gastric cancer cases, 42% of pancreatic ductal adenocarcinoma cases and 43% of biliary-tract cancer cases. Similar results were reported in the study by Wang et al (31), which confirmed the presence of survivin in the sera of 31.5% of CRC patients. In turn, Rohayen et al (32) observed purified recombinant survivin reactions only in 8.2% of CRC patients.…”
Section: Survivin (Pg/ml) -------------------------------------------supporting
confidence: 81%
“…Survivin antibodies were noted in 39.7% of all cancers studied, including 33% cases of CRC, hepatoma and esophageal cancer, 40% of gastric cancer cases, 42% of pancreatic ductal adenocarcinoma cases and 43% of biliary-tract cancer cases. Similar results were reported in the study by Wang et al (31), which confirmed the presence of survivin in the sera of 31.5% of CRC patients. In turn, Rohayen et al (32) observed purified recombinant survivin reactions only in 8.2% of CRC patients.…”
Section: Survivin (Pg/ml) -------------------------------------------supporting
confidence: 81%
“…Otherwise, the expression of serum or plasma antibodies anti-HER2 and MUC1, was found to be help in early detection of other cancers such as lung cancer, myeloma and colorectal cancer (Treon et al, 2000;Chapman et al, 2008;Wang et al, 2012). In all these studies the serum expression of antibodies was higher in patients except in patients with multiple myeloma which was higher in healthy donors (Treon et al, 2000;Chapman et al, 2008;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…We also collected multiple autoantibodies in 42 different combinations for CRC (Table 2). 11-83 The research was mainly undertaken in China (n = 20) and the USA (n = 12), with the remainder in Japan, Germany, Spain, and elsewher...…”
Section: Resultsmentioning
confidence: 99%